Gamification as a trend in organizing professional education of sociologists in the context of distance learning: analysis of practices - Liudmyla Kalashnikova; Iryna Hrabovets; Liudmyla Chernous; Viktoriia Chorna; Arnold Kiv (Academy of Cognitive and Natural Sciences, 2022)
The article identifies the essence of the phenomenon of gamification as a modern trend in distance education, as well as outlines its innovative potential based on the analysis of cases of introduction of gamification elements in the training of sociology students at Kryvyi Rih State Pedagogical University and Petro Mohyla Black Sea National University. Case studies were performed using an analytical model of gamification, which includes four interrelated elements: actors, content, effects, context.